Impact of Generative AI on Student Learning in Higher Education using Robust Assessment Metrics Framework - Adesola M. Falade; Ayobami E. Mesioye (Methods in Science and Technology Studies, 2026)
The rapid emergence of Generative Artificial Intelligence (GAI) has transformed the landscape of higher education, influencing pedagogy, assessment, and student learning experiences. Despite its widespread adoption, a significant research gap persists regarding the empirical measurement of its impact on specific learning outcomes. While GAI tools are widely adopted, existing assessment frameworks often fail to distinguish between machine-generated efficiency and genuine cognitive development. This study addresses this gap by developing the Robust Assessment Metrics Framework (RAMF), evaluated through a mixed-methods approach involving students and faculty (N=295) at McPherson University. Quantitative findings reveal a significant "Efficiency-Cognition Trade-off": while frequent GAI usage significantly enhances task efficiency (p < 0.001), it correlates with a statistically significant decline in critical thinking (p < 0.01) and self-reported originality (p < 0.01). Interestingly, regression analysis shows that AI literacy and institutional policy clarity are stronger predictors of academic confidence than usage frequency. This suggests a psychological "confidence paradox" where students feel more capable despite lower cognitive engagement. Qualitatively, thematic analysis highlights a shift toward "shortcut learning" that necessitates a move from product-oriented to process-oriented evaluation. The RAMF introduces expert-validated protocols such as the ‘30/70 Synthesis Rule’ and "Process Logs," to safeguard academic rigor. This research provides institutional leaders with an expert-validated framework proposed for institutional trial to shift from product-oriented to process-oriented assessment in the AI era. By focusing on the interplay between human agency and algorithmic assistance, this research offers broader implications for pedagogical redesign in an AI-saturated academic environment.